x^2-13x+36=0

Multiply the exponent of

xby 2givingThe answer is

x^2 evaluates to

Multiply

xand13Multiply

xand1

The

xjust gets copied along.The answer is

x

x13*x evaluates to

13xx^2-13*x evaluates to

The answer is

x^2-13*x+36 evaluates to

The final answer is

To solve (find the roots of) the quadratic equation =0:

First, we'll attempt to factor this quadratic equation as a trinomial.

is a valid trinomial that might be factorable.

This trinomial can be factored. Here is it in factored form:

=(x-9)(x-4)

With the two factors found, we now solve the equations:

x-9=0 andx-4=0.

Solving

x-9=0, we get that x=9

Solving

x-4=0 and, we get that x=4Therefore, x=

9and x=4are the roots to the quadratic equation